Financial Benefits from JIT Adoption: Effects of Customer Concentration and Cost Structure - Balakrishnan, Ramji; Linsmeier, Thomas J.; Venkatachalam, Mohan (The Accounting Review, 1996)
[This paper examines whether firms exhibiting improved inventory utilization subsequent to JIT adoption achieve a corresponding increase in their Return on Assets (ROA) and whether firm-specific characteristics affect such ROA responses. On average, we do not find a significant ROA response to JIT adoption. Cross-sectionally, JIT adopting firms with a diffuse customer base have a superior ROA response relative to both adopting firms with a high degree of customer concentration and their matched control firms. Evidence is consistent with a superior ROA response for firms with lower inventory turns in the adoption year, particularly for work-in-process inventory. Data do not support the prediction that firms with lower committed costs will report a greater ROA response than firms with a higher proportion of committed costs.]